Questioning the Metacognitive Reading Strategies in an English-Medium Instruction (EMI) Setting - Çoban, Mustafa; Razı, Salim (Springer Science and Business Media B.V., 2022)
English-medium instruction (EMI) has already been an inseparable component of numerous tertiary education systems across the globe. As a receptive skill, reading is considered to be the main input source in EMI contexts. Given the gap between departmental studies and intensive English programs, the complexity of reading texts in EMI courses can place a burden on university students, especially for those who cannot employ effective reading strategies. Therefore, this mixed method study aims to investigate the metacognitive reading strategies used by students at a technical university in Turkey where EMI is implemented in engineering departments. To triangulate the quantitative data retrieved from a scale called Metacognitive Reading Strategies Questionnaire (MRSQ), a focus group interview session was conducted with six participants. For data analysis, NVivo 12 Pro and Amazon AWS Transcribe were used. The quantitative results showed that the participants tended to use analytic strategies (determining the meaning of critical words, visualizing descriptions and drawing on self-knowledge) more than pragmatic ones (re-reading for better comprehension and making notes to help them remember). However, the qualitative results revealed that the interviewed participants favored pragmatic strategies: they made notes, underlined critical information, translated and used margins for notetaking. In addition, the participants highlighted the importance of guidance by their EMI instructors as regards the use of strategies. The pedagogical implications of this study encourage the implementation of both analytic and pragmatic reading strategies in EMI settings and highlight the importance of PD (Professional Development) activities to train subject teachers in implementing strategies in their courses. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Analytic strategies; English-Medium Instruction (EMI); Metacognitive reading strategies; Pragmatic strategies; Tertiary education